A bibliometric analysis of linguistic research on COVID-19 - Peng, Zhibin; Hu, Zhiyong (Frontiers in Psychology, 2022)
Research on COVID-19 has gained the attention of world’s scholars since the outbreak of the pandemic. There are already some literature reviews conducted based on scientometric indicators or bibliometric analyses. However, there is no literature review on the state of linguistic research on COVID-19 till now. This study undertakes the studies published in SSCI and A&HCI journals pertaining to linguistic performance using the CiteSpace software. The overall performance of the documents was described, and then document co-citations, keyword co-occurrence and keyword clusters were visualized via CiteSpace. The main research topics were the influences of COVID-19 on language education, speech-language pathology and crisis communication. The results of the study indicate that there are some linguistic theories which have been not paid enough attention to in the linguistic study on COVID-19, such as Conceptual Metaphor Theory, Critical Discourse Analysis, Pragmatics, Corpus-based discourse analysis, etc.